1991
DOI: 10.1002/jcp.1041490222
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cobalamin metabolism are associated with the altered methionine auxotrophy of highly growth autonomous human melanoma cells

Abstract: Our aim was to identify the biochemical defect responsible for the inability of highly growth autonomous human tumor cells to proliferate in culture medium devoid of methionine, but containing homocysteine and 5-methyletrahydrofolic acid. We have adopted the terms "homocysteine-responsive" and "homocysteine-nonresponsive" to describe cells which can or cannot proliferate in methionine-free homocysteine-supplemented medium. Using a panel of genetically related homocysteine-responsive and -nonresponsive human me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 14 publications
0
17
0
1
Order By: Relevance
“…Each of these cofactors might be defective in tumour cells, leading to less MET synthesis. Studies have shown that some MET-dependent cell lines lack sufficient cobalamin to assure HCY methylation (Liteplo et al, 1991;Pezacka et al, 1992). MET dependency might also be a result of the low availability of HCY that would be metabolized in the transsulphuration pathway (Figure 1), which requires cystathionine j-synthase.…”
Section: Discussionmentioning
confidence: 99%
“…Each of these cofactors might be defective in tumour cells, leading to less MET synthesis. Studies have shown that some MET-dependent cell lines lack sufficient cobalamin to assure HCY methylation (Liteplo et al, 1991;Pezacka et al, 1992). MET dependency might also be a result of the low availability of HCY that would be metabolized in the transsulphuration pathway (Figure 1), which requires cystathionine j-synthase.…”
Section: Discussionmentioning
confidence: 99%
“…MET-dependent tumour cells appear to synthesize MET from HCY by an active MET synthase, but at levels not adequate to both sustain growth and meet their high transmethylation requirements (Judde et al, 1989). The most likely biochemical defect leading to MET dependency is thought to be related to the synthesis and availability of methylcobalamine, which is directly involved in the transfer of methyl groups from 5-methyltetrahydrofolate to HCY (Liteplo et al, 1991;Fiskerstrand et al, 1994).…”
mentioning
confidence: 99%
“…Однако на культуре клеток карциносаркомы Уокера показано, что 5-MTHF не влияет на метиониновую зависимость [83]. На примере клеток меланомы, лейкоза и глиомы GaMg дискутируется спорный ме-ханизм развития метиониновой зависимости через нарушение метаболизма кобаламина со снижением активности MTR [84][85][86]. …”
Section: механизмы развития метиониновой зависимости в опухолевых клеunclassified